IMPLEMENTATION OF DIGITAL SIGNATURE FOR RESEARCH PAPER LEGALIZATION, AUTHENTICATION AND RATIFICATION CASE STUDY: TRAINING CENTER FOR NATIONAL CYBER AND CRYPTO AGENCY - Siswanto, Budi; Surgawiwaha, Dian (PEOPLE: International Journal of Social Sciences, 2019)
At The Training Center for The National Cyber and Crypto Agency, at the end of every course programs, the students are given a task to write scientific papers. Then those papers must be ratified by the seminar committee using their wet signatures as a sign of ratification of documents. But the drawback of using wet signatures is that often difficult to get committee signatures as they are not always in the office. To overcome this problem, we’ll discuss the uses of digital signature for student’s papers ratification. This research begins by describing a digital signature and how it can replace a wet signature. Then we present the design of a scheme for implementing a digital signature that can be applied for papers authentication and ratification. Retrieval of the research data is done through in-depth observations in the process of ratifying student’s scientific papers at The Training Center for The National Cyber and Crypto Agency. The result of this study is the application of digital signatures as a substitute solution for wet signatures on student’s scientific papers ratification.